Numerical Studies of the Gas-Solid Hydrodynamics at High Temperature in the Riser of a Bench-Scale Circulating Fluidized Bed - Maximilian J. Hodapp; Jhon J. Ramirez-Behainne; Milton Mori; Leonardo Goldstein (International Journal of Chemical Engineering)
The hydrodynamics of circulating fluidized beds (CFBs) is a complex phenomenon that can drastically vary depending on operational setup and geometrical configuration. A research of the literature shows that studies for the prediction of key variables in CFB systems operating at high temperature still need to be implemented aiming at applications in energy conversion, such as combustion, gasification, or fast pyrolysis of solid fuels. In this work the computational fluid dynamics (CFD) technique was used for modeling and simulation of the hydrodynamics of a preheating gas-solid flow in a cylindrical bed section. For the CFD simulations, the two-fluid approach was used to represent the gas-solid flow with the k-epsilon turbulence model being applied for the gas phase and the kinetic theory of granular flow (KTGF) for the properties of the dispersed phase. The information obtained from a semiempirical model was used to implement the initial condition of the simulation. The CFD results were in accordance with experimental data obtained from a bench-scale CFB system and from predictions of the semiempirical model. The initial condition applied in this work was shown to be a viable alternative to a more common constant solid mass flux boundary condition.